Effectiveness of a program in the reduction of cardiovascular risk factors.: Efectividad de un programa en la reducción de los factores de riesgo cardiovascular. - Montalvo, Raul (2024)
Introduction: The prevalence of cardiovascular risk factors such as overweight, dyslipidemia, hypertension (HTN) and diabetes mellitus (DM2) has increased in recent decades, so there are multiple programs to reduce this prevalence. Objective: To evaluate the early effect of a program aimed at reducing cardiovascular risk factors in secondary education teachers. Methods: An intervention study was carried out based on the application of physical exercises and nutritional education workshops once a week for three consecutive months. General data were recorded and the lipid profile, glucose, blood pressure and body composition were quantified by using the bioimpedance balance, at the beginning of the intervention and 3 months later in the intervention group and the control group. To evaluate the effect of the program, the averages were compared and the level of significance was defined at 0.05. Results: Of a total of 556 people who completed the study, the average age was 44 years; overweight and obesity was at 65.5%. In the intervention group, an increase in HDL cholesterol was evident (OR 1.409; 95% CI 1.213-2.089; p=0.037); decrease in total weight (OR 1.135; CI5% 1.081-1.424; p=0.041) and decrease in visceral fat (OR 2.651; CI5% 1.781-3.271; p=0.024). Conclusion: The intervention program based on weekly exercise and nutritional educational workshop is effective in the short term in reducing some cardiovascular risk factors.